Combination of metagenomic next-generation sequencing and morphology for identifying Coccidioides immitis: a case report - Hong Liu; Kaixin Zhou; Chaoran Zhong; Ming Guan (Frontiers in Medicine)
Coccidioidomycosis is a systemic infection caused by the dimorphic fungus Coccidioides spp., endemic to the Southwestern United States and Central and South America. In this article, we report a case of Coccidioides immitis-induced meningitis in a 27-year-old man who was experiencing recurrent fever and headache. His cerebrospinal fluid (CSF) biochemical markers indicated an infection in the central nervous system. However, repeated routine cultures of the CSF for bacterial detection were all negative. Only metagenomic next-generation sequencing (mNGS) detected low reads of C. immitis. To verify the mNGS results, the Clinical Microbiology Laboratory in Huashan Hospital optimized its culture conditions. Ultimately, 12 days after sampling, the fungal bottle containing the cerebrospinal fluid tested positive. Furthermore, the diagnosis of C. immitis was then confirmed by smear staining combined with morphological characteristics of the colony, which provided an important etiological basis for clinical diagnosis and treatment. As coccidioidomycosis is a rare disease in China, its pathogen-specific diagnostic methods are limited. In this case, we combined two universal methods, mNGS and traditional morphological observation, to confirm the diagnosis. This combined strategy is critical for quick and accurate diagnosis.